Peran Kontrol Diri Terhadap Perilaku Kenakalan Remaja Pada Siswa SMP di Sekolah Pinggiran Kota Samarinda - Arinda, Icha Bunga; Haq, Aniq Hudiyah Bil; Hamka, Hamka (Universitas Trunojoyo Madura, 2025)
This study aims to reveal the extent of the influence of self-control on juvenile delinquent behavior in junior high school students in the suburban school area of Samarinda. The method used is quantitative research with a research population of junior high school students in three suburban schools in Samarinda which include SMPN 26 Samarinda, SMPN 28 Samarinda and SMPN 29 Samarinda, while the sample of this study amounted to 313 students selected through simple random sampling technique. Data collection was carried out offline and online using two instruments that had been modified by the author, namely the self-control scale adapted from Shofiatun's research (2021) and the juvenile delinquency scale adapted from Anggraini's research (2019). Data analysis was carried out using simple linear regression to test the hypothesis that had been formulated. The results of the research analysis found that self-control has a negative and significant effect on juvenile delinquent behavior by 30.3% while the remaining 69.7% is influenced by other factors. That means, the higher the student's self-control, the lower the juvenile delinquent behavior and vice versa, the low self-control of students can be related to the increase in juvenile delinquent behavior. As for the findings of the identification that has been carried out related to various types of juvenile delinquent behavior, it is found that the juvenile delinquent behavior that has the greatest frequency is speaking harshly with a total of 216 students or 8.97%.